THE USE OF PROCESSED OR SYNTHETIC MINERALS IN THE PREPARATION OF FOOD, PHARMACEUTICALS, COSMETICS AND OTHER PRODUCTS - Τσιραμπίδης, Α. (Bulletin of the Geological Society of Greece, 2004)
The contribution of many minerals, processed or synthetic, in the industrial development and thus in the improvement of man's life has increased their use in new industrial sectors displacing other traditional products, mainly of organic origin which however contaminate the environment. The content of this paper is related to the industries of food, pharmaceuticals, chemicals (paper, paints, detergents, cosmetics) and building materials. Twelve different products of wide consumption have been selected, of Greek or foreign origin, which were analysed in order to confirm the participation of common and special minerals even in small amounts. Quantities of these products were heated at 350° C (or 250° C) for three hours in order to destruct the organic constituents and remove the water and all volatile compounds from them. The solid residue of the studied products varied from 10% to 78%. Great decrease (about 50%) was noticed in the solid residue of the edible products (chocolate and biscuits) when they were heated at different temperatures of equal time duration, probably because of the incomplete burning of the organic constituents. Processed or synthetic mineral constitute the greater percentage by weight of the wash detergent (78%) and the child's clay (70%). The solid residue of these products is composed of one to four different minerals. In the milk chocolate the presence of an inorganic phase at 3,2 A and 2,2 A is undetermined. In the biscuits (of Greek and Spanish origin) the presence of only one inorganic phase, halite, was confirmed. The Kaopectate and the Terramin, trade names of additives with base of kaolinite and Ca-montmorillonite respectively, which are used in similar products or pharmaceuticals, were not detected, probably because of their decomposition during the thermal processing of the products. The presence of ground limestone or marble in the chicken food was confirmed mainly with the participation of calcite and minor dolomite. In addition, in this food, minor amount of fluorite was detected, too. The anatase as carrier and the rhodochrosite as pigment are the inorganic constituents of stomach tablets (of English origin). Fluorapatite and diaspore are the mineral phases contained in the toothpaste (of Italian origin) with the first mineral in more than double amount. The anatase and the talc are contained about in equal amounts in the face make up (of USA origin) with minor hematite which gives the brown-red colour. Synthetic zeolite A, sodium sulphate, sodium carbonate and minor K-feldspar were detected in the wash detergent of cloths. The sodium tripolyphosphate (STPP) compound was not detected. The use of zeolite A was internationally imposed for environmental reasons against the phosphoric compounds. Synthetic T1O2 (from the rutile processing) is the unique inorganic constituent of the paint in this study. The solid residue of the phototypic paper (of Sweden origin) is composed almost completely of CaC03 (GCC or PCC) and minor mica. Finally, the child's clay is mainly composed of calcite and minor amounts of kaolinite and orthoclase